Pemanfaatan Visualisasi 3D Berbasis Learning Stations untuk Meningkatkan Hasil Belajar dan Keaktifan Murid Kelas III SD Muhammadiyah Argosari - Haristuti Hanung Arifanny; Azzamul Fadhly Muhammad; Isti Nurhayati (Dewantara : Jurnal Pendidikan Sosial Humaniora, 2026)
This study was motivated by low student participation and learning outcomes among third-grade students of SD Muhammadiyah Argosari in learning landform materials. Previous instruction was mainly teacher-centered and relied on worksheets, causing passive behavior, limited engagement, and difficulty understanding abstract landform concepts. The study aimed to describe the implementation of 3D visualization media integrated with the Learning Stations model and analyze its impact on participation and learning outcomes. A descriptive approach combining quantitative and qualitative data was applied. The participants were 20 third-grade students of SD Muhammadiyah Argosari, Bantul Regency. Data were collected through observation, tests, questionnaires, and documentation. The results indicated that 3D visualization media combined with the Learning Stations model effectively improved student participation and learning outcomes. The average score increased from 66.55 in the pretest to 84.85 in the posttest, while learning mastery rose from 45% to 85%. Participation improved in enthusiasm, discussion, curiosity, and engagement during learning. In addition, 93% of students enjoyed the learning process. These findings show that this integration creates a more active, concrete, and enjoyable environment for elementary students to understand landform concepts.